Eletrossíntese orgânica e caracterização do copolímero poli(anilina-co-4-aminofenol) para aplicação em imunossensor de biomarcador de distúrbios da tireoide - Segatto, Mônica Silva (2021)
Electrochemical biosensors are versatile tools for clinical diagnosis, because among so many advantages, they have good sensitivity and selectivity and low response times. The use of conducting polymers as a matrix for immobilization of biomolecules contributes to the biocompatibility of biosensors, as there is exposure of functional groups that provide a favorable microenvironment. The objective of this work was the preparation and characterization of a new polymeric material for application in biosensors, the copolymer derived from the monomers 4-aminophenol and aniline, named as poly(aniline-co-4-aminophenol) – 4-PANAP. The copolymer was electropolymerized on the surface of graphite electrodes, applying cyclical potential scans in an acid medium containing the comonomer mixture. The results of electrochemical, morphological and structural characterization indicated the formation of a new material with hybrid characteristics between poly(4-aminophenol) (P4AP) and polyaniline (PANI). 4-PANAP showed redox peaks in the P4AP region with charge density similar to PANI, with an intermediate behavior between the two against electron transfer. The morphology of 4-PANAP resulted in forms of interconnected fibers, different from the globular PANI and stretched fibers of P4AP. Infrared spectra reveal that both characteristic functional groups of P4AP and PANI remain in 4-PANAP. The application in biosensors was evaluated against the development of an electrochemical immunosensor to detect the thyroid hormone 3,5,3′-triiodothyronine (T3). The study of the immunosensor for T3 allowed the evaluation of the best conditions for electrosynthesis of the copolymer against the detection of T3, which was the electropolymerization with an equimolar monomeric mixture (1:1), in the potential range of –0.1 to +1, 2 V at 50 mV s–1. From the construction of the analytical curve, a linear relationship between the anodic current and the T3 concentration range was reached, in the working range of 0.2 to 8.8 ρg mL−1, with a detection limit of 0.60 pg mL−1 and a limit of quantification of 1.80 pg mL−1. The proposed platform kept 90% of the analytical signal after a period of 60 days, whose results were promising for real applications, achieving success in the performance of the platform.